2011
DOI: 10.4257/oeco.2011.1503.08
|View full text |Cite
|
Sign up to set email alerts
|

Plankton Richness and Abundance in Several Different Hydrological Situations in Lakes Lateral to a River: A Case Study in the Mouth Zone of a Tributary into a Tropical Reservoir

Abstract: A descriptive analysis of the responses of plankton from lakes lateral to a river in its mouth zone into a tropical reservoir to water level variations is presented. Three situations were reported: 1) a comparison of species richness and diversity and of algae population abundance in prolonged drought and in periods of connection of lakes to the river, 2) the spatial distribution of abundance and richness of Rotifera species in four isolated water bodies formed by fragmentation of a lateral lake during a perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
2
8
0
1
Order By: Relevance
“…These results are in line with the suggestions and findings of several authors (Amoros & Bornette, 2002;dos Santos Bertoncin, Pinha, Baumgartner, & Mormul, 2019;Henry et al, 2011;Mayora, Devercelli, & Giri, 2013), meaning that the homogenizing effect of the flood pulse is not a general rule and must be adjusted to the kind of situation, aquatic organism and river. For example, while zooplankton beta diversity and environmental heterogeneity decrease during flooding (Bozelli, 1992;Bozelli, Thomaz, Padial, Lopes, & Bini, 2015), fish dispersal is likely to increases and fish assemblage homogenization may occurs later, during low water phases.…”
Section: )supporting
confidence: 91%
“…These results are in line with the suggestions and findings of several authors (Amoros & Bornette, 2002;dos Santos Bertoncin, Pinha, Baumgartner, & Mormul, 2019;Henry et al, 2011;Mayora, Devercelli, & Giri, 2013), meaning that the homogenizing effect of the flood pulse is not a general rule and must be adjusted to the kind of situation, aquatic organism and river. For example, while zooplankton beta diversity and environmental heterogeneity decrease during flooding (Bozelli, 1992;Bozelli, Thomaz, Padial, Lopes, & Bini, 2015), fish dispersal is likely to increases and fish assemblage homogenization may occurs later, during low water phases.…”
Section: )supporting
confidence: 91%
“…Studies performed in South American floodplain systems have found higher abundances of some zooplanktonic species during dry periods or limnophase (Brandorff & Andrade 1978, Saunders & Lewis Jr. 1989, Paggi & De Paggi 1990, Lansac-Tôha et al 1993, Lima et al 1998, Rossa & Bonecker 2003, De Paggi & Paggi 2007Henry et al 2011), when the hydrodynamic conditions were more stable, thus promoting primary productivity which supports large populations of zooplanktonic organisms due to higher water residence time (Baranyi et al 2002). In contrast, during potamophase, we observed a dilution effect in which organisms were more dispersed in the water column (Bozelli 2000, Lansac-Tôha et al 2009).…”
Section: Macrothrix Elegans Sars 1901 Copepodamentioning
confidence: 97%
“…The biodiversity and conservation of such reservoirs are particularly sensitive to climate change (Moss et al, 2009) and are considered as stressed environments (Leira and Cantonati, 2008 and references therein;Naselli-Flores, 2003;Henry et al, 2011;Perbiche-Neves et al, 2011). Compared with natural lakes, artificial waterbodies are subject to severe fluctuations in the water level from seasonal and interannual climatic variations, as well as abstraction for irrigation, hydropower and drinking water.…”
Section: Introductionmentioning
confidence: 99%